EVALUATION OF USEING SOME AQUATIC ALGAE AND PLANT MATERIALS IN COMMON CARP ( CYPRINUS CARPIO) LARVAES DIETS - YOUSIF, U. H.; ABDULKARRIM, L. M.; YOUNIS, K. H. (Iraqi Journal of Aquaculture, 2022)
Filamentous algae , Blue green algae and Alpha alpha were used in common carp ( Cyprinus carpio ) larvaes diets at different percentages (10 , 24 , 34)% from diet weight to Alpha alpha and (34) % to filamentous algae and blue green algae .The larvaes were cultured in average weight (0.00089)g and average length (0.7)cm on six aquaria at (63) larvae/aquarium . The higher growth rates , survival rates and the increase of larvae weight and length were found in the diets (5) and (6) (34%) filamentous algae and blue green algae respectively in comparable to diet (1) , the length rates was (1.4,1.33)cm and the weight rates was (0.035, 0.036)g and the survival rates (77.7, 71.4)% and the specific growth rates (3832.58 , 3944.94) % and the relative growth rates (17.48 , 17.61) %wt/day respectively compared to (10.1)cm length rate , (0.016)g weight rate , (54)% survival rate , (1697.75)% specific rate and (13.75) %wt/day relative growth rate to diet (1) . There are a significant differences (P < 0.05) between the diets (5 , 6) and the other diets in larvaes length , weight , growth rates and survival rates .